(untitled) (European journal of volunteering and community-based projects, 2025)
Purpose: While most studies have investigated healthcare responses to emergent health needs during COVID-19 crisis, scant research has addressed accounting for the pandemic’s impact on healthcare personnel’ quality of life. Methodology: A survey has been conducted to gather data from professionals working for a Northern Italian public local healthcare organization, to understand their perceptions on their self-efficacy, work environment, working conditions and quality of life during COVID19. Findings: Positive work environment was found to reduce negative effects of COVID19 on the quality of life of healthcare personnel. At the same it brought a better achievement of work-life balance. Nevertheless, increased self-efficacy caused a sense of malaise due to the heavy workload and additional responsibilities. Originality/Value: This study takes a broader stance on “accounting” as non-financial information relevant for sustainability decision making and adopts such a perspective to account for the COVID-19 pandemic’s impact on healthcare professionals operating in a local health organization; this approach allows to inform sustainable human resource management practices in the light of SDGs in such knowledge-intensive organizations.